Role of exosome microRNA in breast cancer - Wang Qu (Cancer Translational Medicine, 2017)
Exosomes are nanovesicles derived from multiple cell types and could be isolated from various bodily fluids, such as blood and saliva. The molecular contents of exosomes have been proved to reflect their parent cell origins. MicroRNA (miRNA), a large family of small, noncoding RNAs, is enriched in exosomes and could regulate the expression of their target genes. Numerous studies have indicated that aberrant expression level of exosomal miRNAs is closely related to the onset of multiple diseases, including cancer. For example, the studies show that tumorigenesis, drug resistance, invasiveness, and metastasis in breast cancer, are partly mediated by exosome miRNAs, functioning as tools for cell-to-cell communication. Furthermore, several investigations have revealed the immense potential of exosome miRNAs to serve as prognostic and diagnostic biomarkers, whereas certain miRNAs could even be on the target list of novel therapies for cancer, including breast cancer. Due to the lack of a standard approach, exosome miRNAs have not been successfully made into clinical practice, yet. In this review, we highlight the major progressions in exosome miRNA research on breast cancer and the current limitations/challenges in its clinical implementation. Promising and potential applications of exosomal miRNAs will also be addressed.